Systematic Review of The PICO Method Regarding The Effectiveness The Effectiveness of Giving Guava Juice (Psidium guajava) Women In Increasing Hemoglobin Levels - Nurfitri; Margiyanti, Norma Jeepi; Sari, Desi Premita; Wilujeng, Ayu Rosanti (Future Science, 2024)
Hemodilusi that occurs during pregnancy makes pregnant women tend to experience a decrease in hemoglobin levels of up to 10g/dl. This increases the risk of anemia in pregnant women. Guava juice (Psidium guajava) is known to contain iron and other important nutrients that can help increase hemoglobin levels. This systematic review uses the PICO (Population, Intervention, Comparison, Outcome) method to evaluate the effectiveness of giving guava juice (Psidium guajava) to pregnant women in increasing hemoglobin levels. Literature searches were carried out using the PubMed and GoogleScholar databases with relevant keywords (Giving Guava Juice (Psidium guajava) to Anemic Pregnant Women to Increase Hemoglobin Levels), the systematically and gradually eliminated literature that did not meet the inclusion criteria and presented in the form of a PRISMA Diagram. From 21 pieces of literature that met the inclusion criteria, it was found that the administration of guava juice (Psidium guajava) could consistently increase hemoglobin levels in pregnant women. These studies also show that guava (Psidium guajava) can increase the iron intake needed during pregnancy. This systematic review concludes that giving guava juice (Psidium guajava) can effectively increase hemoglobin levels in pregnant women and this intervention can be used as a preventive, curative, and rehabilitative measure which is believed to have no long-term determental pharmacological effects for pregnant women. Recommendation can be used in future research to conduct larger and more controlled studies to validate the positive results that have been found in previous studies.